Hypertrophic cardiomyopathy in an extremely preterm infant. Issue 3 (9th March 2021) - Aiyengar, Apoorva; Howarth, Claire; Pereira, Sujith
Abstract : We present a case of an extreme preterm infant (Baby X) born at 24-week gestation. The echocardiogram showed evidence of hypertrophic cardiomyopathy (HCM) and a patent ductus arteriosus (PDA). There are a number of well-known causes of neonatal HCM including genetic, metabolic and endocrine. PDA is commonly present in preterm infants, and this can contribute to cardiac remodelling and result in cardiac changes mimicking HCM. Furthermore, medications such as steroids can also cause HCM through various mechanisms. A careful consideration of all the different aetiologies for HCM is important for appropriate management of such cases. This report examines the evidence in the literature for the above differential diagnoses and highlights the challenges in diagnosing the underlying cause of HCM in a preterm infant.